Down East Maine, Prince Edward Island, Nova Scoti and the Gaspe - Sagent F. Collier (Cambridge, MA Houghton Miller Company, Boston, 1953)
With its splendid photographs and knowledgeable text, Sargent Collier's new book is the first of its kind to catch the full flavor of Acadia, the most charming corner on North American. It is a place of island'-dotted harbors, jagged cliffs and snug fishing villages and a colorful past that has spilled over into the present.
Keywords: Maine; Quebec, Canada; Nova Scotia; Prince Edward Island